Duties performance level of Sana'a University teaching staff - Dawood Al-Hidabi; Raja'a Al-Hamdani (University of Science and Technology, Yemen, 2010)
Abstract                                                                                               This study aims at identifying duties performance level of Sana'a University teaching staff. It also tries to find out if the variables: faculty, gender, and scientific rank would make any difference in duties  performance level. The descriptive approach was adopted,  and the population of the study included all working teachers at the faculties of Sana'a University who are 1205 teachers. The sample of the study was 242 teaching staff. The research tool was a questionnaire composed of three categories which are teaching, scientific research and community service. Findings reveal that duties performance level of the teaching staff in the category of teaching is highly achieved, scoring first among other categories. Duties performance level of the teaching staff in the category of scientific production is averagely achieved, and duties performance level of the teaching staff with regard to  theses supervision is significantly achieved. Community service is averagely achieved scoring last among all categories.  There were no significant differences in duties performance level of the teaching staff that can be attributed to gender, faculty or scientific rank.